2011
DOI: 10.1371/journal.pone.0017458
|View full text |Cite
|
Sign up to set email alerts
|

The Populus Class III HD ZIP Transcription Factor POPCORONA Affects Cell Differentiation during Secondary Growth of Woody Stems

Abstract: The developmental mechanisms regulating cell differentiation and patterning during the secondary growth of woody tissues are poorly understood. Class III HD ZIP transcription factors are evolutionarily ancient and play fundamental roles in various aspects of plant development. Here we investigate the role of a Class III HD ZIP transcription factor, POPCORONA, during secondary growth of woody stems. Transgenic Populus (poplar) trees expressing either a miRNA-resistant POPCORONA or a synthetic miRNA targeting PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 57 publications
(107 reference statements)
5
91
0
Order By: Relevance
“…Zhou et al also predicted that vascular defects induced by miR165 overexpression is linked with an alteration of positional signal, likely mediated by auxin [33]. More recently, a Populus CORONA/ATHB15 was also reported to be involved in hormone-related gene expression [36].…”
Section: Mir165/166-mediated Auxin Biosynthesis and Signaling In Regumentioning
confidence: 99%
“…Zhou et al also predicted that vascular defects induced by miR165 overexpression is linked with an alteration of positional signal, likely mediated by auxin [33]. More recently, a Populus CORONA/ATHB15 was also reported to be involved in hormone-related gene expression [36].…”
Section: Mir165/166-mediated Auxin Biosynthesis and Signaling In Regumentioning
confidence: 99%
“…Consistently, Du et al (2011) and Ong and Wickneswari (2012) reported this gene as being a negative regulator of xylem development in poplar and acacia, respectively. In a similar way, among the WOX family, a WOX8-like gene was detected in cluster 2.…”
Section: Degs Involved In Lw Developmentmentioning
confidence: 54%
“…as a negative regulator of vascular tissue development under the control of miRNA165/166 (Ong and Wickneswari 2012). On the contrary, an miRNAresistant POPCORONA has been suggested to be involved in the upregulation of cellulose biosynthesis-related genes, but also with the down-regulation of lignin deposition-related genes in poplar (Du et al 2011).…”
Section: Degs Involved In Ew Developmentmentioning
confidence: 99%
“…Furthermore, transgenic poplar trees expressing either a miRNA-resistant P O P C O R O N A o r a s y n t h e t i c m i R N A t a rg e t i n g POPCORONA have been used to infer the function of POPCORONA during secondary growth: the synthetic miRNA-mediated knockdown of POPCORONA expression resulted in abnormal lignification in pith cells, whereas the overexpression of a miRNA-resistant POPCORONA delayed the lignification of xylem and phloem fibers during secondary growth. The misexpression of POPCORONA was also shown to result in a coordinated change in gene expression within a previously described transcriptional network regulating cell differentiation and cell wall biosynthesis and in the expression of hormone-related genes associated with fiber differentiation (Du et al 2011).…”
Section: Wood Formationmentioning
confidence: 82%